Toward More Efficient and Effective Public Social Spending in Central America - Acosta, Pablo A.; Almeida, Rita; Gindling, Thomas; Lao Pena, Christine (World Bank, Washington, DC, 2017)
Central America has come a long way both in terms of economic and political stability. Increasingly the region is focusing on implementing productivity-enhancing reforms as well as supporting reductions in poverty and inequality. This report analyzes recent trends in public social spending in Central America from 2007 to 2014, conducts international benchmarking, examines measures of the effectiveness and efficiency of social spending, and discusses the quality of selected institutions influencing this spending. We examine total social spending, as well as detailing its four components: public spending on the education, health, and social protection and labor (SPL) sectors.